Oscar Wilde’s “False Notes”: Dorian Gray and English Realism - Kent, Julia (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis essay situates Wilde’s Picture of Dorian Gray in relation to a common pattern in Victorian novels—the tendency to compare highly regulated English characters with unstable, and immoral, French ones. I argue that the well-known chapter on the “yellow book,” which incorporates from J.-K. Huysmans’s A Rebours a pattern of cosmopolitan consumption, productively disrupts mechanized patterns of consumption that Wilde explicitly associates with the English character and English novel-reading. At the same time, Dorian Gray also remains critical of the ways in which this French structure of characterization is a distinctly cultural form and therefore potentially limits individual autonomy.